2009
DOI: 10.1038/embor.2009.201
|View full text |Cite
|
Sign up to set email alerts
|

Np95 interacts with de novo DNA methyltransferases, Dnmt3a and Dnmt3b, and mediates epigenetic silencing of the viral CMV promoter in embryonic stem cells

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits distribution, and reproduction in any medium, provided the original author and source are credited. This license does not permit commercial exploitation without specific permission.Recent studies have indicated that nuclear protein of 95 kDa (Np95) is essential for maintaining genomic methylation by recruiting DNA methyltransferase (Dnmt) 1 to hemi-methylated sites. Here, we show that Np95 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
152
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 28 publications
7
152
0
Order By: Relevance
“…We have already shown that H3K27me3 is present on this promoter along with its specific methyltransferase EZH2 (Pancione et al, 2010b); here, we provide evidence that H3K9me2 and H3K9me3 are engaged along with Suv39H1 to silence PPARG in CRC cells, in line with recent reports showing that CRC progression correlates with higher levels of Suv39H1 and the presence of these repressive histone marks on promoter sequences (Fullgrabe et al, 2011;Varier and Timmers, 2011). Consistently, UHRF1 depletion is associated with PPARG re-expression through DNA demethylation at the promoter region and H3K9 and H3K27 demethylation, likely due to displacement of EZH2, MeCP2 and Suv39H1, confirming previous data on their physical interactions with UHRF1 (Unoki et al, 2004;Meilinger and Fellinger, 2009;Alhosin et al, 2011). Our data support that PPARG epigenetic deregulation is coordinated by UHRF1 through both DNA and histone methylation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We have already shown that H3K27me3 is present on this promoter along with its specific methyltransferase EZH2 (Pancione et al, 2010b); here, we provide evidence that H3K9me2 and H3K9me3 are engaged along with Suv39H1 to silence PPARG in CRC cells, in line with recent reports showing that CRC progression correlates with higher levels of Suv39H1 and the presence of these repressive histone marks on promoter sequences (Fullgrabe et al, 2011;Varier and Timmers, 2011). Consistently, UHRF1 depletion is associated with PPARG re-expression through DNA demethylation at the promoter region and H3K9 and H3K27 demethylation, likely due to displacement of EZH2, MeCP2 and Suv39H1, confirming previous data on their physical interactions with UHRF1 (Unoki et al, 2004;Meilinger and Fellinger, 2009;Alhosin et al, 2011). Our data support that PPARG epigenetic deregulation is coordinated by UHRF1 through both DNA and histone methylation.…”
Section: Discussionsupporting
confidence: 73%
“…High UHRF1 levels are associated with a more advanced tumor grade (grades 3 and 4), as recently shown in lung, bladder and prostate cancers (Meilinger and Fellinger, 2009;Phe et al, 2010;Alhosin et al, 2011). High UHRF1 expression is also associated with a shorter survival only in advanced stages (stages III-IV).…”
Section: Uhrf1 and Pparg In Colon Tumorigenesismentioning
confidence: 68%
See 1 more Smart Citation
“…In this model, the methyltransferase is recruited to a specific genomic site by directly recognizing nucleosomal DNA or histones [13-15, 18, 25], or alternatively through other adaptor proteins such as Dnmt3L [13,23], G9a [26][27][28], Np95 [29] and PML-RAR [30]. The localized Dnmt3 is then allosterically activated to methylate nearby cytosines upon the binding of an unmodified H3K4 N-terminus to the PHD domain.…”
Section: Discussionmentioning
confidence: 99%
“…Such retroviral transgene silencing may result from the activation of potent repressor factors or the reduction of certain activating factors after directly reprogramming somatic cells to pluripotent states (Hotta and Ellis, 2008). In addition, CMV promoter activity has been shown to be progressively silenced in pluripotent stem cells (Xia et al, 2007;Meilinger et al, 2009). In rAAV2.3m-mediated cell reprogramming, whether transgene silencing resulted from the activation of certain endogenous potent repressor or from the reduction of CMV promoter activity in rAAV-iPS cells remains elusive.…”
mentioning
confidence: 99%